La dialectique de l'absence et de la présence dans la création poétique : l'exemple de la poésie française - Litsardaki, Maria (Quêtes littéraires, 2012)
Considering poetry as a literary form in close relation with absence and scarcity; this paper deals with some of the most frequent and significant forms of absence that appear in poetic texts. The physical absence of the other, due either to death or to the distance between the two individuals, is the most common kind in lyric poetry. Modern poetry often deals with Gods’ absence, which represents an important loss for the contemporary human being, trying to understand or face it. There is also the lack of inspiration and words with efficient expressive capacity that make poets suffer. However, poetry is the only way in which they express their situation and create a meaningful language. Finally, absence in poetry is also a fundamental sign of its generic specificity in connection with the means that it uses, as well as with its printed representation on paper, especially in the contemporary production. In all cases, poetry, based on the dialectic of being – not being, operates as a material, sensible and intellectual presence, which like the primordial logos fillsthe vacuum, eliminates absence and scarcity, generates and animates the human world and en-riches it with presence and meaning.